2009
DOI: 10.1073/pnas.0906198106
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and public health

Abstract: Evolution and its elements of natural selection, population migration, genetic drift, and founder effects have shaped the world in which we practice public health. Human cultures and technologies have modified life on this planet and have coevolved with myriad other species, including microorganisms; plant and animal sources of food; invertebrate vectors of disease; and intermediate hosts among birds, mammals, and nonhuman primates. Molecular mechanisms of differential resistance or susceptibility to infectiou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 52 publications
(52 reference statements)
0
38
0
1
Order By: Relevance
“…Moreover, most of these species found are well known producers of mycotoxins, common contaminants of foods and feeds [11]. In contrast to other studies [24,27] that showed birds exclusively as vectors of human or animal fungal (yeasts and filamentous fungi) pathogens, most of our isolates represent plant pathogens and/or food contaminants. On the other hand, in accordance to data reported by Tsiodras et al [27], birds sampled in the present study were found to be carriers of different species of yeast (such as Cryptococcus spp.)…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Moreover, most of these species found are well known producers of mycotoxins, common contaminants of foods and feeds [11]. In contrast to other studies [24,27] that showed birds exclusively as vectors of human or animal fungal (yeasts and filamentous fungi) pathogens, most of our isolates represent plant pathogens and/or food contaminants. On the other hand, in accordance to data reported by Tsiodras et al [27], birds sampled in the present study were found to be carriers of different species of yeast (such as Cryptococcus spp.)…”
Section: Discussionmentioning
confidence: 60%
“…The recent studies carried out on the microbial populations transported by birds have been mainly related to safety aspects [24,27], since birds contribute to disseminate various microorganisms in the environment [22]. Birds may play a defining role in long distance movement of microorganisms; for example, in the case of yeasts, it has been shown that insects may transport cells within approximately 10 km [9], while migratory birds are effective at longer distances [7].…”
Section: Introductionmentioning
confidence: 99%
“…Public health considers the health effects of individuals interacting with environments, including nutrition, physical activity, climate, and social determinants of health in the broadest sense. Our modern understanding of evolution can be very useful for public health, and public health offers opportunities to understand many evolutionary phenomena, ranging from pathogen transmission and evolution to the constraints that leave us unable to cope effectively with many aspects of modern environments [16,17].…”
Section: Public Healthmentioning
confidence: 99%
“…While evolutionary theory and human evolutionary biology have long been viewed as disconnected from the day-to-day practice of medicine, it has become increasingly clear in recent years that evolutionary biology has many practical applications in medicine and public health (Nesse and Schiffman 2003;Trevathan et al 2008;Gluckman et al 2009;Williams 2009;Nesse et al 2010;Omenn 2010;Pearlman 2013;Alcock and Schwartz 2011;Gluckman and Bergstrom 2011;Stearns 2011Stearns , 2012. For example, understanding human evolutionary history and the resulting patterns of human genetic diversity within and across populations can improve diagnosis, treatment, and preventative care (Bolnick et al, in review).…”
Section: Recommendations For Medical Educationmentioning
confidence: 99%
“…Medical school faculty and students should learn to identify the key social and structural determinants of health that should be targeted for intervention, and they should learn to design and implement structural interventions in clinical, community, and public policy contexts. Medical schools should also provide cultural competency training using the newest and most effective evidence-based models of cultural competency (Carpenter-Song et al 2007;Kumagai and Lypson 2009;Coria et al 2013;Metzl and Hansen 2014;Metzl and Roberts 2014).Recommendation #4: Key aspects of evolutionary theory and human evolutionary biology should be incorporated into the medical curriculum, focusing on how knowledge of evolution improves a physician's ability to prevent, diagnose, and treat disease.While evolutionary theory and human evolutionary biology have long been viewed as disconnected from the day-to-day practice of medicine, it has become increasingly clear in recent years that evolutionary biology has many practical applications in medicine and public health (Nesse and Schiffman 2003;Trevathan et al 2008;Gluckman et al 2009;Williams 2009;Nesse et al 2010;Omenn 2010;Pearlman 2013;Alcock and Schwartz 2011;Gluckman and Bergstrom 2011;Stearns 2011Stearns , 2012. For example, understanding human evolutionary history and the resulting patterns of human genetic diversity within and across populations can improve diagnosis, treatment, and preventative care (Bolnick et al, in review).…”
mentioning
confidence: 99%